2021
DOI: 10.1186/s13046-021-02151-x
|View full text |Cite
|
Sign up to set email alerts
|

The emerging role of ISWI chromatin remodeling complexes in cancer

Abstract: Disordered chromatin remodeling regulation has emerged as an essential driving factor for cancers. Imitation switch (ISWI) family are evolutionarily conserved ATP-dependent chromatin remodeling complexes, which are essential for cellular survival and function through multiple genetic and epigenetic mechanisms. Omics sequencing and a growing number of basic and clinical studies found that ISWI family members displayed widespread gene expression and genetic status abnormalities in human cancer. Their aberrant ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(36 citation statements)
references
References 150 publications
0
29
0
Order By: Relevance
“…ISWI is a member of the SWI2/SNF2 family of chromatin remodeling factors and is found in several different chromatin remodeling complexes in Drosophila [ 1 ]. In vivo, ISWI complexes are involved in the regulation of important physiological activities, such as gene transcription, heterochromatin formation, and X chromosome inactivation [ 2 ]. Among the six known ISWI complexes in Drosophila , NURF, NoRC, and ToRC are significantly involved in transcriptional activation, whereas RSF, ACF, and CHRAC use their nucleosome remodeling activity to close gaps in the nucleosome array during chromatin assembly or after division, thereby improving chromatin fiber stability and foldability [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…ISWI is a member of the SWI2/SNF2 family of chromatin remodeling factors and is found in several different chromatin remodeling complexes in Drosophila [ 1 ]. In vivo, ISWI complexes are involved in the regulation of important physiological activities, such as gene transcription, heterochromatin formation, and X chromosome inactivation [ 2 ]. Among the six known ISWI complexes in Drosophila , NURF, NoRC, and ToRC are significantly involved in transcriptional activation, whereas RSF, ACF, and CHRAC use their nucleosome remodeling activity to close gaps in the nucleosome array during chromatin assembly or after division, thereby improving chromatin fiber stability and foldability [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…27 Degraders 3-6 were synthesized according to Scheme 2, using pomalidomide-based cereblon-targeting E3 ligase ligands. We had also reported a crystal structure of TP-238 (7) with BPTF (PDB ID: 7KDZ). 28 Overlaying the cocrystal structures of TP-238 and compound 1 (Figure 2B) indicated that the pendant N(CH3)2 group in TP-238 provides a similar exit vector to the amine in compound 1, although the longer chain in TP-238 may provide more conformational flexibility.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, the GCN5 bromodomain stabilizes the SWI/SNF complex on chromatin. 6 In the less-studied ISWI family, 7 NURF recognizes chromatin through its largest subunit BPTF, 8 and CERF contains the CECR2 bromodomain-containing protein. 9 BPTF, CECR2 and GCN5 are members of the class I bromodomain family (Figure 1B) and their role in nucleosome remodeling makes them important targets for anticancer therapy.…”
Section: Introductionmentioning
confidence: 99%
“…Based on interactome data, HCAR1 binds to different transcriptional factors from INO80, SWI/SNF and ISWI ATP-dependent chromatin remodeling complexes such as INO80b, SMARCA5, SMARCC1 and BPTF (Hasan and Ahuja, 2019); these interactions were observed with the activated and non-activated receptor, suggesting a potential constitutive role of HCAR1 in modulating their activity in a metabolic-dependent manner. While these chromatin remodelers are significantly miss-regulated in many cancers (Lu and Roberts, 2013) , (Prendergast et al, 2020) , (Li et al, 2021), N-HCAR1 activated by higher concentration of lactate seen in tumor (Warburg effect) could alter their activity (in favor of cancer promotion).…”
Section: Discussionmentioning
confidence: 99%